الدّخيل في تفسير كشف الأسرار وهتك الأستار للإمام جمال الدين الصفدي سورة الأنعام أنموذجًا: دراسة تحليلية: The Intruder in the Book Of ‘Kashf Alʼasrār Wa Hatk Al-Astār’ of Al-Imām Jamāl Al-Dīn Al-Ṣafadī: Sūrah Al Anaam as a Model: An Analytical Study - Abdullah Snh , Mohammed Salmeen; Zekkoub , Abdelali Bey; Mohammed Abdo , Yousef (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
لقد تميز منهج الإمام الصفدي –رحمه الله تعالى- بقبوله للعقل والنقل كدليلين أساسيين في الدين، وباستشهاده من التوراة والإنجيل مع اعتقاده بتحريفهما، وهذا المنهج يُظهر الحاجة الماسة إلى دراسة الدخيل في تفسيره، فجاءت هذه الدراسة مبينة للدّخيل في هذا التفسير. والهدف الرئيس الذي سعى البحث لتحقيقه هو: بيان الدّخيل في تفسير كشف الأسرار وهتك الأستار للإمام الصفدي من سورة الأنعام أنموذجاً. واعتمد الباحث في هذه الدراسة على المنهج الاستقرائي التحليلي؛ لتتبع مواضع الدخيل في تفسير الإمام الصفدي، ثم المنهج الاستنباطي؛ لاستخراج أنواع الدخيل التي تم الوقوف عليها. وكان من أهم نتائج هذه الدراسة: أن تفسير الإمام الصفدي يعد من أنفس كتب التفسير، إذ يتميز بغزارة المادة العلمية، وقد حوى تفسيره فوائد جمة لا توجد مجموعة في كتاب واحد، وأيضًا اعتناء الإمام الصفدي بالإسرائيليات في تفسيره وأكثر من إيراده لها، وذلك من خلال نصوص التوراة والانجيل المقتبسة، وأيضًا قلة إيراد الإمام الصفدي لما أُثر عن النبي ﷺ من الحديث، وكذلك أقوال السلف من الصحابة والتابعين. هذا وإن الإمام الصفدي يرى ضرورة القول بالرأي والأخذ به في تفسير كلام رب العالمين، وقد تناولت الدراسة ثمانية أمثلة مما يعد دخيلاً تم تنقيته من تفسير الإمام الصفدي، من خلال سورة الأنعام، مبينية وجه الدخيل فيها، ودراسته دراسة علمية. Al-Imam al-Safadi’s approach is distinguished by his acceptance of reason and transmission as two basic guides in the religion, And by his martyrdom from the Torah and the Injil, even though he believed that they had been distorted. This approach shows the urgent need to study the intruder in his interpretation. This study came to clarify the intruder in this interpretation. The main objective that this research seeks to achieve; the explanation of the intruder in the interpretation of the ‘Kashf al-Asrār Wahatk al-Astār’ of al-Imām Jamāl Al-Dīn al-Ṣafadī and its implications in Sūrah Al Anaam as a model. The researcher’s method in this study is the inductive and analytical method. Among the most important results of this study were: The interpretation of Imam Safadi is one of the most important books of interpretation, It is characterized by the abundance of scientific material, His interpretation contained many benefits that there is no collection in one book. Also, Imam al-Safadi’s used too much the narrations of people of book in his interpretation, as well as he used texts from the Torah and the Injil. Also, despite his lack of mentionnig what was reported from the Prophet from the hadith, Likewise, the sayings of the Salaf from the Companions and the Followers. It is from that that Imam Safadi he sees the necessity of saying the opinion and adopting it in the interpretation. The study showed that the extraneous narrations pose a significant danger to the Islamic faith. The study dealt with eight intruders based in the interpretation of Imam al-Safadi - may God Almighty have mercy on him - from Surah Al Anaam.